Determinants of self-rated health of Francophone seniors in a minority situation in Canada - Alimezelli, Hubert Tote; Leis, Anne; Karunanayake, Chandima; Denis, Wilfrid (Linguistic Minorites and Society, 2013)
Résumé La tendance actuelle montre que les institutions des services de santé et les gouvernements répondent de façon inadéquate aux besoins de plus en plus nombreux d’accès aux services de santé par les populations vieillissantes du Canada et d’autres pays développés. Après l’analyse de l’enquête post-censitaire 2006 de Statistiques Canada sur la Vitalité des Minorités de Langue Officielle, cette étude démontre qu’outre l’age, et en plus d’autres déterminants, les barrières linguistiques auxquelles font face les aînés de langue officielle en situation minoritaire affectent davantage l’autoévaluation de leur santé. Cette étude suggère quelques pistes de solution dont la compréhension des réalités contextuelles, l’amélioration de l’environnement linguistique et des services de santé dans la langue minoritaire. Mots-clés : déterminants de la santé, statut minoritaire, santé perçue, minorités linguistiques, aînés Abstract Current trends show that governments and health institutions in Canada and other developed nations are responding inadequately to the growing need for health services of the increasingly aging population. The Analysis of Statistics Canada’s 2006 post-census Survey on the Vitality of Official Language Minorities show that in addition to age and other socio-demographic determinants, linguistic barriers affect the self-rated health of seniors of official languages living in a minority situation. This study suggests among other things a greater understanding of Official language minorities’ contextual realities, the improvement of both the linguistic environment and services in the minority language. Keywords: health determinants, minority status, self-rated health, linguistic minorities, older adults

Language as an important determinant of poverty in the aging Francophone minority population in Canada - Bouchard, Louise; Sedigh, Golnaz; Batal, Malek; Imbeault, Pascal; Makvandi, Ewa; Sylva de la Vega, E. (The International Journal of Aging and Society, 2013)
Six cycles of the Canadian Community Health surveys (CCHS) from 2001 to 2009 were used to compare the income and health of the minority French-speaking aging population (over 65 years of age) to the majority English-speaking group in Canada, excluding Quebec. A sequential multivariate logistic regression analysis showed that men and women of the minority French-speaking population of this age group, living in Canada outside the province of Quebec, are more likely to be in the poorest income quintile than their English-speaking counterparts. This disparity remains significant even after controlling for residence (province and urban/rural), household makeup (living alone or not), immigration status, education, employment, health status, chronic diseases, and restrictions in activities. Independently of other key socio-demographic factors modulating health, our results also show that being in the poorest income quintile is associated with a poor self-perceived health, a finding that was more prevalent in the French-speaking aging population living in situation of minority.